Low Revenue Factors In Kuala Kedah Fishery Industry - Ng, Wei Chet (2014)
Malaysia is ranking at 16th of fish production in the world and 11th in Asia countries. (Department of Statistic Malaysia, 2013). However, the Gross Domestic Product (GOP) of marine product has grown only 0.2% since year 2008 and 2012. With our focus to Kedah marine fish that is obtained from Statistic Malaysia 2013, the quantity recorded has dropped 6.87% from 106.5 ton (2009) to 99.2 ton (2012). Furthermore, govemment has announced to deplete the subsidy the diesel pnce to fishery industry in year 2013. Fishing boat owners have voiced out that this implementation lower their revenue (The New Straits Time, Nov 2013). Other than that, implementation of district of employment of foreign crews for fishing boat to type B boat «40 GRT) has made the fishermen and fishing boat owner having ill difficulty to get helper during the trip to sea.